Evaluation of quantitative and quality traits in diverse carrot (Daucus carota) genotypes to identify high-performing inbred lines for breeding programmes - LONE, SAMEENA; NARAYAN, SUMATI; HUSSAIN, KHURSHEED; MASOODI, KHALID Z; MALIK, M A; KHAN, F A; YADAV, S K; NAZIR, NAGEENA; MAQBOOL, MARYAM; NARAYAN, RAJ (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during the winter (rabi) season of 2021 and 2022 at Sher-e-Kashmir University of Agricultural Sciences and Technology-Kashmir, Shalimar, Srinagar, Jammu and Kashmir to evaluate the quantitative and quality traits in diverse carrot (Daucus carota L.) genotypes and to identify high-performing inbred lines for breeding programmes. Fifty-two treatments comprising of 50 genotypes and 2 checks, procured from various sources were assessed for several quantitative and qualitative traits in augmented block design (ABD). The analysis of mean values revealed that no single genotype excelled in all the traits studied. However, certain genotypes demonstrated exceptional performance in specific economically significant traits. For instance, SKAU-C-5 showed superiority in plant height and petiole length, while SKAU-C-41 excelled in foliage length, root length, average root weight and root yield/ha. SKAU-C-48 stood out for traits such as the number of days to the first and last root harvest and SKAU-C-30 was notable for its high total carotenoid and anthocyanin content. Since no genotype exhibited outstanding performance across all traits, genotypes with the highest number of desirable characteristics could be utilized in a carefully designed hybridization programme to develop superior lines in subsequent segregating generations.